A Randomized Clinical Trial Comparing Eyetronix Flicker Glass and Patching for Treatment of Amblyopia in Children Reveals Similar Improvements in Vision - Min, Seung Hyun; Chen, Shijia; Xu, Jinling; Chen, Bingzhen; Chen, Hui; Wang, Yuwen; Zhou, Jiawei; Yu, Xudong (Frontiers in Neuroscience, 2021)
Purpose: Recently, Eyetronix Flicker Glass (EFG) has been introduced as a novel treatment for amblyopia. It alternatively deprives the visual input of each eye rapidly (ex. 7 Hz). However, whether it is comparable to standard patching therapy is unclear. In this randomized clinical trial, we evaluate the efficacy of an EFG therapy as treatment for amblyopia in children and compared it to patching. Methods: We tested 31 children (aged 4-13 years) with amblyopia. They were assigned into one of the two treatment groups and were treated for 12 weeks. The first group was treated with EFG for one hour per day (Flicker Group), and the latter with a standard patch (Patching Group) for two hours per day. We designated changes from baseline in best-corrected visual acuity (BCVA) of the amblyopic eye as our primary outcome. Changes from baseline in other visual outcomes, such as contrast sensitivity, stereopsis and fusional vergence range were measured as secondary outcome. Results: BCVA improved significantly at 12 weeks relative to baseline in both the Flicker (0.13 ± 0.11 logMAR; mean ± SD) and Patching Groups (0.21 ± 0.14 logMAR). However, the improvements were not significantly different between groups (p = 0.13). Contrast sensitivity also significantly improved at 3 and 12 cycles/degree between baseline and 12-week in both groups (p’s < 0.05). However, stereopsis and fusion range did not improve significantly in both groups. Conclusion: An EFG therapy and patching improved BCVA similarly for children with amblyopia at 12 weeks. Both therapies improved the contrast sensitivity at 3 and 12 cpd; however, only patching improved the contrast sensitivity at 6 cpd. Both therapies did not benefit binocular visual functions (stereopsis and fusional vergence range). We believe that EFG can be an additional choice for therapy.